Special educational needs of children and adolescents with epilepsy - Elżbieta Kręcisz-Plis (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Abstract: Introduction: Epilepsy is one of the most common chronic conditions of the nervous system. It occurs in around 0,5-1% of school-aged children. It should be emphasized, that a chronic disease is always a very difficult and stressful situation, not only for a child and their family, but also for teachers who cooperate with them. Purpose: The aim of this research is to draw attention to the school situation of a child with epilepsy, regarding especially to them educational needs resulting from the specificity of the disease.